Mesh r-adaptation for unilateral contact problems - Béal, Pierre; Koko, Jonas; Touzani, Rachid (Zielona Góra: Uniwersytet Zielonogórski)
We present a mesh adaptation method by node movement for two-dimensional linear elasticity problems with unilateral contact. The adaptation is based on a hierarchical estimator on finite element edges and the node displacement techniques use an analogy of the mesh topology with a spring network. We show, through numerical examples, the efficiency of the present adaptation method.
Keywords: unilateral contact; linear elasticity; mesh adaptivity; node movement